From Religious Authority to Character Formation: KH Nasori’s CommunityBased Islamic Education in Tegal Regency, Indonesia - Abdul Fatah (JPI: Jurnal Pustaka Indonesia, 2026)
This study aims to analyze the role of KH Nasori as a local Islamic educational figure in shaping the religious, moral, social, and national character of the Muslim community in Tegal Regency, Indonesia. It responds to the limited scholarly attention given to local ulama as community-based agents of Islamic character education, particularly in regional Muslim societies undergoing socio-religious transformation. This study employed a qualitative figure-study design supported by historical-pedagogical analysis. The primary data were obtained from Abdul Fatah’s biography of KH Nasori, while secondary data were drawn from scholarly literature on Islamic education, character education, pesantren studies, kiai leadership, religious moderation, and community-based education. Data were collected through documentation and library research and analyzed using the interactive model of Miles and Huberman, consisting of data condensation, data display, conclusion drawing, and verification. The findings show that KH Nasori contributed to character formation through personal exemplarity, religious da’wah, classical Islamic text teaching, pesantren-based mentoring, mosque-centered community education, and active engagement in Nahdlatul Ulama. The main character values internalized through these practices include religiosity, sincerity, istiqamah, simplicity, social responsibility, moral courage, moderation, and national commitment. These findings indicate that Islamic character education is not confined to formal institutions or written curricula, but can be cultivated through living moral authority, community engagement, and socio-religious leadership. Since this study relies on biographical and documentary sources, future research should employ oral history, ethnography, or comparative case studies to examine the broader impact of local ulama on community-based Islamic education.